Sustainable Workforce: The Role of Employee Engagement on Perceived Organizational Support to Employee Retention - Zetiara Nurul Sabila; Gumgum Gumelar; Zarina Akbar (Faculty of Psychology, Universitas Semarang, 2024)
Abstract. Retaining talented employees in the competitive pharmaceutical industry becomes crucial for company success. This study explores employee engagement's role as a mediator in the influence of perceived organizational support on pharmaceutical employees' retention. The study method used is quantitative cross-sectional. Purposive sampling was used with 212 employees from private pharmaceutical companies, each with a minimum period of 6 months. Data analysis in research using Mediation Regression Analysis. The mediation analysis results showed p=0.001 (p<0.05) that employee engagement plays a significant role as a partial mediator in the relationship between perceived organizational support and employee retention by 6,6%. This study provides insights into the importance of perceived organizational support and employee retention in enhancing employee engagement, enabling companies to retain talented employees in the pharmaceutical industry.Keywords: employee engagement; perceived organizational support; employee retention